Graft failure after allogeneic islet transplantation in a patient with type 1 diabetes and a high anti‐glutamic acid decarboxylase antibody titer. Issue 5 (1st March 2023) - Kodani, Noriko; Chujo, Daisuke; Terakawa, Aiko; Ito, Kyoji; Inagaki, Fuyuki; Takemura, Nobuyuki; Matsumoto, Shinichi; Tajima, Tsuyoshi; Ohmagari, Norio; Ajima, Kumiko; Takaki, Tadashi; Yamashita, Yzumi; et al.
ABSTRACT: Pancreatic islet transplantation is a β‐cell replacement therapy for people with insulin‐deficient diabetes who have difficulty in glycemic control and suffer from frequent severe hypoglycemia. However, the number of islet transplantations carried out is still limited in Asia. We report a case of allogeneic islet transplantation in a 45‐year‐old Japanese man with type 1 diabetes. Although the islet transplantation was successfully carried out, graft loss was observed on the 18th day. Immunosuppressants were used in accordance with the protocol, and donor‐specific anti‐human leukocyte antigen antibodies were not detected. Autoimmunity relapse was also not observed. However, the patient had a high titer of anti‐glutamic acid decarboxylase antibody from before the islet transplantation, and autoimmunity might thus have affected the β‐cells in the transplanted islet. The evidence is still scarce to reach conclusions, and further data accumulation is required to enable proper patient selection before islet transplantation. Abstract : We report a case of allogeneic islet transplantation in a 45‐year‐old Japanese man with type 1 diabetes, which ended in graft loss on the 18th day. The high titer of anti‐glutamic acid decarboxylase antibody from before the islet transplantation might have affected the β‐cells in the transplanted islet. The evidence is still scarce to reach conclusions, and further data accumulation is required to enable proper patient selection before islet transplantation.